Caeca Microbial Variation in Broiler Chickens as a Result of Dietary Combinations Using Two Cereal Types, Supplementation of Crude Protein and Sodium Butyrate - Borda-Molina, Daniel; Mátis, Gábor; Mackei, Máté; Neogrády, Zsuzsanna; Huber, Korinna; Seifert, Jana; Camarinha-Silva, Amélia (Frontiers in Microbiology, 2021)
The intestinal microbiome can influence the efficiency and the health status of its host’ digestive system. Indigestible non-starch polysaccharides (NSP) serve as substrates for bacterial fermentation resulting in the production of short-chain fatty acids like butyrate. In broiler’s nutrition, dietary crude protein and the presence of butyrate is of special interest for its impact on intestinal health and growth performance. In this study, we evaluated the effect on the microbial ecology of the caeca of dietary supplementations, varying the cereal type (maize and wheat), adequate levels of crude protein (CP) and supplementation of sodium butyrate. The overall structure of bacterial communities was statistically affected by cereal type, crude protein, and sodium butyrate (P= 0.001). Wheat in the diet promotes the presence of Lactobacillaceae, Bifidobacteriaceae and Bacteroides xylanisolvens, that can degrade complex substrates. Maize was positively affecting the abundance of Bacteroides vulgatus. The addition of crude protein was promoting the presence of the family Rikenellaceae while sodium butyrate as feed supplement was positively related to the family Lachnospiraceae. Functional predictions showed an effect of the cereal type and a statistical significance across all supplementations and their corresponding interactions. In this study, the composition of diets affected the overall structure of broilers’ intestinal microbiota. The source of non-starch polysaccharides and thereof the substrate for bacterial fermentation had a stronger stimulus on bacterial communities compared to CP content or supplementation of butyrate.